2001
DOI: 10.1017/s1047951101000087
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated combined anatomical/electrophysiological approach for catheter ablation of atrioventricular nodal reentrant tachycardia in children

Abstract: Atrioventricular nodal reentrant tachycardia was proven during electrophysiologic study in 41 children, aged from 3.7 to 16 years, who were referred for catheter ablation of symptomatic supraventricular tachycardia. Using an abbreviated combined anatomical and electrogram-guided approach for selective ablation of the slow pathway, a steerable ablation catheter was placed at the inferior region of the vestibule of the tricuspid valve close to the orifice of the coronary sinus, with the intention of recording a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…Overall, there was a recurrence rate of 9.1%, which is within the range of 6 to 12% given in the literature . In accordance with the literature, there was a very low recurrence rate of 2.9% in patients with AVNRT , but higher recurrence rates for patients with AVRT or VT . Besides, recurrence rates were significantly higher in right lateral AP, which corresponds well to previous studies reporting higher recurrence rates after ablation of the right free wall AP compared with the left AP .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, there was a recurrence rate of 9.1%, which is within the range of 6 to 12% given in the literature . In accordance with the literature, there was a very low recurrence rate of 2.9% in patients with AVNRT , but higher recurrence rates for patients with AVRT or VT . Besides, recurrence rates were significantly higher in right lateral AP, which corresponds well to previous studies reporting higher recurrence rates after ablation of the right free wall AP compared with the left AP .…”
Section: Discussionsupporting
confidence: 89%
“…Accessory pathways of the right free wall were ablated less successfully compared with the left AP, which is most probably explained by the higher difficulty of finding a stable position for the ablation catheter . Besides, there was a high success rate of 97.2% in children with AVNRT, which also corresponded well to the results reported by several authors (, ). Overall, these findings demonstrate that RFCA has become a remarkably successful treatment for arrhythmia in children.…”
Section: Discussionsupporting
confidence: 84%
“…Recent research has indicated that a combined electrophysiologic and anatomical mapping approach with catheter ablation of the slow pathway can safely and effectively treat atrioventricular nodal reentrant tachycardia (AVNRT) 1–3 . In adults, a site near the coronary sinus ostium along the tricuspid annulus has generally been adopted as the slow pathway target site.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, a site near the coronary sinus ostium along the tricuspid annulus has generally been adopted as the slow pathway target site. Although pediatric references generally support this approach, 1,2 , 4–12 to our knowledge, no studies have specifically examined its appropriateness in developing children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation